2013
DOI: 10.1159/000351635
|View full text |Cite
|
Sign up to set email alerts
|

The Timing of Reconstruction in Severe Mechanical Trauma

Abstract: Serious ocular trauma involving the posterior segment remains rather common and, despite many technological advances in recent years, continues to represent a significant management challenge to the ophthalmologist. One of these challenges is to identify the most optimal timing for the ultimate reconstruction, namely vitrectomy. While it is fairly obvious that suture-closure of the wound of open-globe injuries should be done as soon as possible, it is less clear whether vitrectomy should be performed in the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 35 publications
3
32
0
3
Order By: Relevance
“…He concluded that the earlier the vitrectomy, the higher the risk of intraoperative complications, bleeding, wound leakage, and bad visualization. Conversely, the later the vitrectomy, the higher the incidence and severity of postoperative complications, mainly PVR [22, 23]. However, other authors investigated longer time [24] (mean 49 days) and they concluded that a delayed approach is compatible with good visual prognosis in relatively young patients.…”
Section: Discussionmentioning
confidence: 99%
“…He concluded that the earlier the vitrectomy, the higher the risk of intraoperative complications, bleeding, wound leakage, and bad visualization. Conversely, the later the vitrectomy, the higher the incidence and severity of postoperative complications, mainly PVR [22, 23]. However, other authors investigated longer time [24] (mean 49 days) and they concluded that a delayed approach is compatible with good visual prognosis in relatively young patients.…”
Section: Discussionmentioning
confidence: 99%
“…Sparing the patient a second operation, together with the possibly that a detached retina may be reattached sooner, favours a one-stage intervention [12].…”
Section: Early or Late Vitrectomy?mentioning
confidence: 99%
“…Overall, there are thus good reasons for a two-stage approach [12,13], and the two-stage approach has some clear advantages: If the cornea is involved, the exploratory inspection during the ini-tial surgery may not be optimal for retinal surgery treatment. This may fundamentally jeopardise the success of a retinal surgery intervention, may however also lead to more subtle changes such as a traumatic macular hole being overlooked.…”
Section: Early or Late Vitrectomy?mentioning
confidence: 99%
“…Nyitott szemgolyósérülések esetén minden esetben az érkezést követő lehető legkorábbi primer sebzárás történt az endophthalmitis és az expulzív vérzés kivédése céljából. A sebzárás halasztása (24 óra; például éjszaka helyett munkaidőben történő ellátás) a szakirodalmi adatok szerint növeli az endophthalmitis kockázatát [14][15][16]. Az esetek 70%-ában primer átfogó rekonstrukció történt, vagyis a páciens nem szorult több beavatkozásra.…”
Section: Betegek Módszerunclassified